2013
DOI: 10.1007/s00374-013-0827-1
|View full text |Cite
|
Sign up to set email alerts
|

Herbivory of an invasive slug in a model grassland community can be affected by earthworms and mycorrhizal fungi

Abstract: Invasion of non-native species is among the top threats for the biodiversity and functioning of native and agricultural ecosystems worldwide. We investigated whether the herbivory of the slug Arion vulgaris (formerly Arion lusitanicus; Gastropoda), that is listed among the 100 worst alien species in Europe, is affected by soil organisms commonly present in terrestrial ecosystems (i.e. earthworms—Annelida: Lumbricidae and arbuscular mycorrhizal fungi—AMF, Glomerales). We hypothesized that slug herbivory would b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 58 publications
1
13
2
Order By: Relevance
“…First, the role of earthworms as important ecological engineers in agroecosystems and gardens can be compromised 10 . Reductions in mixing of organic litter within the soil will limit long-term soil microbial activity 9 , effects of earthworms on aboveground herbivores 37 38 39 , soil nutrient cycling and availability, all of which may lead to reductions in plant productivity 40 . Second, pulses of nitrate and phosphate availability following herbicide application could increase the risk of leaching or surface runoff of these nutrients into groundwater systems or adjacent aquatic ecosystems, as long as the crop cover is not yet re-established.…”
Section: Resultsmentioning
confidence: 99%
“…First, the role of earthworms as important ecological engineers in agroecosystems and gardens can be compromised 10 . Reductions in mixing of organic litter within the soil will limit long-term soil microbial activity 9 , effects of earthworms on aboveground herbivores 37 38 39 , soil nutrient cycling and availability, all of which may lead to reductions in plant productivity 40 . Second, pulses of nitrate and phosphate availability following herbicide application could increase the risk of leaching or surface runoff of these nutrients into groundwater systems or adjacent aquatic ecosystems, as long as the crop cover is not yet re-established.…”
Section: Resultsmentioning
confidence: 99%
“…We found that the effects of earthworms on growth and resistance of plants under herbivory were overall negatively correlated ( Figure 4a), as would be predicted by classic plant defence theory (Herms & Mattson, 1992;Züst & Agrawal, 2017). An increasing number of studies indicate that earthworms could indirectly influence the performance of herbivores such as phloem-feeders by predominantly affecting plant size, vigour and nutrient content (Eisenhauer & Scheu, 2008;Scheu et al, 1999;Trouve et al, 2014), and to a lesser extent by changes in plant secondary chemistry (Francis, Lognay, Wathelet, & Haubruge, 2001;Katsanis, Rasmann, & Mooney, 2016;. For example, Cao et al (2016) showed that the green peach aphid (Myzus persicae) performed better on an enhanced amino acid:…”
Section: Earthworm Effects On the Trade-offs Between Plant Performamentioning
confidence: 99%
“…In addition to these proven growth-promoting effects (e.g. van Groenigen et al, 2014), recent studies have highlighted that earthworms can also benefit plants by increasing their ability to resist herbivore attacks (Lohmann, Scheu, & Muller, 2009;Trouve, Drapela, Frank, Hadacek, & Zaller, 2014;Wurst, 2013;Wurst, Allema, Duyts, & Van Der Putten, 2008).…”
mentioning
confidence: 99%
“…Additionally, the time of day [ 25 , 26 ] and the availability of suitable shelters affect slug activity [ 25 , 27 ]. Some studies also observed that earthworms [ 28 , 29 ] or plant diversity [ 30 ] affected the extent of herbivory by slugs.…”
Section: Introductionmentioning
confidence: 99%